Merancang Model Kewirausahaan Mandiri Mahasiswa Berbasis Sumber Daya Lokal dan Teknologi (KMB-SLoT) - Galib, Mukhtar; Suryo Putro, Guntur; Arfiany, Arfiany; Yasni, Yasni (ABDI DAYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Student entrepreneurship development in higher education often falls into top-down approaches that are generic and create a dependency on external grants. Consequently, many student businesses lack sustainability and differentiation because they are detached from the local potential surrounding them. This paper aims to design a self-reliant entrepreneurship model for students as a solution to these challenges. The proposed model is Self-Reliant Entrepreneurship Based on Local Resources and Technology (SRE-LoRT/KMB-SLoT). This conceptual framework emphasizes a paradigm shift from external dependency to an "inside-out" approach by utilizing contextual assets and technology as the primary drivers of independence. Through integrative phases—including contextual discovery, local-technology hybridization, and networked independent operations—the model is designed to build adaptive capacity and psychological independence (entrepreneurial self-efficacy) among students. It is expected that the KMB-SLoT model can serve as a reference for universities in designing community service programs that are more effective, rooted in locality, and sustainable